Peran Motivasi Kerja Dan Kepemimpinanterhadap Kinerja Karyawan Dalam Perspektif Psikologi Manajemen - Zikra Olivia; Marhayani, Marhayani; Yuci Aidil Hanabi; Merika Setiawati (CV. ITTC INDONESIA, 2025)
This article discusses the role of management psychology in understanding employee performance through the perspectives of work motivation and leadership. Management psychology emphasizes the importance of psychological aspects in managing human resources to achieve organizational effectiveness. This study aims to examine theoretically the concepts of work motivation, leadership, and employee performance, as well as their interrelationships within organizational contexts. The method used in this study is a literature review by analyzing relevant books and scientific journal articles related to management psychology, motivation theories, leadership theories, and employee performance. The findings indicate that work motivation and leadership are two crucial factors that significantly influence employee performance. High work motivation encourages employees to perform optimally, while effective leadership creates a supportive work environment that enhances employee commitment and productivity. The implication of this study highlights the importance of applying management psychology principles in organizational practices to improve employee performance sustainably.